The quick and easy way to effective speaking - "Carnegie, Dale" (Vermilion London, 1998)
It takes you step by step through:-Acquiring basic public speaking skills-Building confidence -Speaking effectively the quick and easy way -Earning the right to talk -Vitalising your talk -Sharing the talk with the audience as well as organisation and presentation skills